The Effectiveness of Collaborative E-Learning-Based Learning in Reducing Student Misconceptions on Heat in East Java High Schools During Merdeka Belajar - Heny Ekawati Haryono; Moh Zayyadi; Iib Marzuqi; Ida Kaniawati (Postgraduate, University of Mataram, 2024)
This study aims to determine the effectiveness of Collaborative E-learning-Based Learning (KABEL) to remedy student misconceptions for heat in high schools in East Java during merdeka belajar. The study used a pre-experimental design, specifically a one-group pre-test post-test design. The study includes a sample of 290 10th-grade students who were randomly chosen from different high schools in East Java. The data collection instrument consists of 20 multiple-choice questions, each with 3 alternative answers and open-ended reasons. The average percentage of student misconceptions was 94.67% before and 39.33% after remediation. The Mc Nemar test showed a significant improvement in student conceptual understanding after remediation, as evidenced by a chi-square value (X2) of 11.16, which exceeded the critical chi-square value (X2table) of 3.84 for a degree of freedom (df) of 1 and a significance level (α) of 5%. The obtained proportion value of 0.56 shows a moderate effectiveness of the direct instruction model with animation media in addressing student misconceptions.